Bank performance and shari’ah supervisory board attributes by Islamic banks: Does bank size matter? - Nomran, Naji Mansour; Haron, Razali; Hassan, Rusni (IIUM Press, 2017)
This study aims to provide new empirical evidence on whether the impact of Shari’ah Supervisory Board (SSB) characteristics on Islamic Banks (IBs) performance can be affected by the size of the bank by using a sample of 25 banks for the period from 2007 to 2015. Six SSB characteristics were employed as explanatory variables which are (size, cross-membership, educational qualification, reputation, experience and change in the composition). By employing random-effects GLS and GMM method for a robustness check, it is found that four SSB characteristics (size, cross-membership, educational qualification and change in the composition) significantly affect the performance of IBs when the full sample is examined. However, the findings vary when the sample is divided into two subsamples, large and small bank. Four SSB characteristics (size, cross-membership, reputation and experience) are found to play an important role in enhancing the performance of large IBs while only (reputation and experience) significantly affect the performance of small IBs. This confirms that the impact of SSB characteristics on performance concentrates more on large IBs as compared to the small banks. Thus, there is a lack of Shari’ah governance practices in the small IBs in Malaysia and Indonesia as compared to the large banks.